Italian youth mobility during the last two decades: an overview in eight selected EU countries - Gallo, Gerardo; Staniscia, Barbara (Hungarian Geographical Bulletin, 2017)
The international mobility of young people from Europe’s Mediterranean countries has become an important topic in scientific debate. The issue has major reverberations in the national media since youth outflows – not adequately compensated for by return flows or new inflows – can undermine the economic and social sustainability of development processes in the countries of origin. The 2007–2008 financial and economic crisis, contributed significantly to intensifying those outflows and reducing the return flows. This paper focuses on the international mobility of young Italians during the past two decades. After addressing the problem of existing data sources and their comparability, our analysis, in terms of spatial distribution, will be concentrated on eight EU destination countries presenting three different sets of socio-economic characteristics: the UK, Germany and Sweden (characterised by high mobility, high income, and high capacity for attracting immigration); Latvia, Romania and Slovakia (characterised by high out mobility, medium-low income, and low capacity for attracting immigration) and Ireland and Spain (characterised by high mobility, mediumhigh income, and a temporally and spatially discontinuous capacity for attracting immigration). In terms of geographical distribution, our analysis will consider the most represented places of origin in Italy at the provincial level. Our study provides an overview of international outflows of young Italians, considering destination countries, places of origin, gender, marital status and age. These results could be used by scientists and policymakers in dealing with the challenge of maximizing the advantages of mobility for individuals while minimizing costs in terms of social and economic sustainability.